The HuR CMLD-2 inhibitor exhibits antitumor effects via MAD2 downregulation in thyroid cancer cells - Allegri, Lorenzo (Sci Rep, 2019)
Hu antigen R (HuR) is indeed one of the most studied RNA-binding protein (RBP) since its fundamental role both in tumorigenesis and cancer progression. For this reason, downregulation in HuR protein levels or inhibition of HuR biological function are, nowadays, attractive goals in cancer research. Here, we examined the antitumor effects of CMLD-2 in four thyroid cancer cell lines (SW1736, 8505 C, BCPAP and K1). Indeed, CMLD-2 competitively binds HuR protein disrupting its interaction with RNA-targets. 35 μM CLMD-2 produced a significant downregulation in thyroid cancer cell viability, coupled to an increase in apoptosis. Moreover, CMLD-2 treatment hindered both migration and colony formation ability. MAD2 is a microtubules-associated protein known to be greatly overexpressed in cancer and correlating with tumor aggressiveness. Furthermore, MAD2 is known to be a HuR target. CMLD-2 treatment induced a strong MAD2 downregulation and rescue experiments depicted it as a key effector in HuR-mediated in cancer. Altogether, these data contributed to foster HuR inhibition as valid antineoplastic treatment in thyroid cancer, highlighting MAD2 as a novel therapeutic target.